The Strategy to Increase the Production of Freshwater Aquaculture Industry in Pandeglang Regency - Viriawan, Triadi Chandra; Nurilmala, Mala; Pandjaitan, Nora H (Institut Pertanian Bogor, 2026)
Freshwater aquaculture small and medium enterprises (SMEs) are industrial activities within the fisheries aquaculture sub-sector that focus on freshwater fish farming. The output production from upstream to downstream fishery activities provide opportunities to increase community income and welfare. These activities in the fishery industry contribute economic value that supports equitable development on a regional scale. The aims of research on freshwater aquaculture SMEs are: (1) Identifying and evaluating the production value of regional yields; (2) Evaluating the potential profit through a feasibility study of the aquaculture business; and (3) Formulating strategies for SMEs to increase the production of the freshwater aquaculture industry. Qualitative data was obtained through questionnaires administered to seven expert respondents from the Banten Marine and Fisheries Service (Dinas Kelautan dan Perikanan) and the Pandeglang Fisheries Service (Dinas Perikanan). The formulation of the aquaculture industrial strategy generates by the strengths, weaknesses, opportunities, and threats (SWOT) method that result in strategy which focused on maintaining the quantity, quality, and marketing of product yields based on the increase of freshwater aquaculture SMEs production in the Pandeglang Regency area